Pengaruh Model Flipped Classroom terhadap Kemampuan Representasi Matematika Ditinjau dari Cuirosity Belajar Matematika di SMK GKPS 2 Pematangsiantar - Martinus H Sihotang; Theresia Monika Siahaan; Yoel Octobe Purba (Journal on Education, 2023)
This study aims to determine whether there is an effect of the Flipped Classroom Model on the Ability of Mathematical Representation in View of the Curiosity of Learning Mathematics at SMK GKPS 2 Pematangsiantar. The method used in this study is an experimental method using a quasy experimental design in the form of a pretest-posttest control design. The sample consisted of two classes, namely the experimental class which was treated with the Flipped Classroom learning model and the control class which was given the conventional learning model. Data was collected by observation, test and documentation methods. Data analysis used normality test, homogeneity test, and hypothesis testing. The results of testing the hypothesis obtained tcount> ttable or where the thitiung on the test was obtained 2.758> 2.01808 and tcount on the questionnaire (questionnaire) obtained tcount obtained 6.275> 2.01808. This means that H0 is rejected and Ha is accepted. So it shows that there is an influence of the Flipped Classroom Model on the Ability of Mathematical Representation in terms of the Curiosity of Learning Mathematics at SMK GKPS 2 Pematangsiantar.